The Correlation Between the Level of Student Learning Independence with Students Learning Outcomes in VIII Grade Students at MTs Mambaul Falah Bawean Gresik on 2017/2018 Academic Year - Isbani Isbani (Universitas Islam Jember, 2019)
Independence refers to the belief in the ability of oneself to solve problems without special assistance from others, reluctance to be controlled by others, can carry out their own activities and solve problems themselves. While the learning outcomes are changes in individual behavior that includes cognitive, affective, and psychomotor aspects. The researcher took class VIII MBI of MTs Mambaul Falah and showed the mathematic value of students exceeding KKM. This study was used to determine whether there is a correlation between the level of independence of learning and the learning outcomes of mathematics. The research approach used is a quantitative approach with a type of correlation. Based on the results of the study, the rtable value at ? = 5% and db = 15 is 0.514 so that rcount<rtable (0.279 <0.514) then the null hypothesis is accepted and the alternative hypothesis is rejected, the value is 0.279 and is located at 0.20-0.40 which indicates low interpretation. Keywords: learning independence, learning outcomes